Effect of 6-week BFRT combined with IASTAM therapy on international standard dancers with chronic ankle instability - Liu, Yang; Wang, Ying (Frontiers in Physiology, 2024)
Objective: This study aims to observe the effects of exercise intervention (low-load ankle muscle strength training with blood flow restriction training（BFRT） equipment and balance training with blood flow restriction training equipment) combined with instrumentation therapy (Instrument-assisted soft tissue mobilization, IASTM) on ankle function, joint range of motion, and strength in sports dancers with chronic ankle instability（CAI）. This study aims to provide an evidence-based approach to rehabilitation for athletes by comparing the effects of combination therapy approaches to traditional ankle strength and stability training. Result:There was no significant difference in the participant characteristics of the three intervention groups. In terms of Cumberland Ankle Instability Tool（CAIT） scores, within-group comparisons showed that the scores after the first intervention and at the 6-week mark were significantly higher than before the intervention (P < 0.05). Between-group comparisons revealed that the combined intervention group had higher CAIT scores than the other two groups after the 6-week intervention.Regarding the FAAM functional scores, all three interventions significantly improved ankle joint function in patients with chronic ankle instability (P < 0.05), with the BFRT group showing significantly higher FAAM - Activities of Daily Living scale（FAAM-ADL） scores than the control group (P < 0.05). Both the combined and BFRT groups also had significantly higher FAAM-SPORT scores after the first intervention compared to the control (P < 0.05). In terms of ankle range of motion improvement, the combined intervention group showed a significant increase in ankle joint motion after the intervention (P < 0.05), particularly in the improvement of dorsiflexion ability (P < 0.05). As for ankle strength enhancement, all three intervention groups experienced an increase in ankle strength after the intervention (P < 0.05), with the combined intervention group showing a significant improvement in both dorsiflexion and inversion strength compared to the control group (P < 0.05). Conclusion: BFRT combined with IASTM, isolated BFRT, and conventional ankle strength and stability training significantly improve stability, functionality, and strength in CAI patients. The combined intervention demonstrates superior efficacy in improving ankle range of motion compared to isolated BFRT and conventional approaches.